Alcantarillado combinado: Población "La Celica". - Lomas Ch., Jimena A. (2005)
The Celica enclosure belongs to the Sierra region in Ecuador, with an altitude that varies between 620 and 570 m.s.m.m. The population of Celica is located north-west of the province of Pichincha, in the canton of Pedro Vicente Maldonado. It is limited by the Silanche and Pitzará rivers The main access road is a third order road, from the mainland and good conditions throughout the year, which joins the streets that make up the site. This enclosure is based on the slopes of the hill on which the main road is built, conforming the basins of the rivers that limit it, with its separation of waters on this road